2017
DOI: 10.2503/hortj.okd-021
|View full text |Cite
|
Sign up to set email alerts
|

Difference between Nighttime and Daytime UV-B Irradiation with Respect to the Extent of Damage to Perilla Leaves

Abstract: Although ultraviolet-B (UV-B) light (280-315 nm) irradiation effectively controls spider mites in horticultural crop production, it also causes plant damage, leading to growth suppression, changes in morphology, and leaf scorching. However, sensitivity to UV-B varies among plant species. Here, we assessed the effect of UV-B on growing perilla (Perilla frutescens var. crispa) plants. Three experiments were conducted. In the first experiment, plants of the variety 'Akachirimenshiso' were grown in a plastic house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…As UV-B light sources are being used as artificial lighting to improve phytochemical concentration and to control flowering, it is desirable to provide illumination to an extent that does not impair growth rate and phenotype quality. Using the same light source as that used in the present study, Ota et al [ 21 ] did not report any effect on plant growth under conditions of exposure to 3 h of illumination at 0.05 W m −2 (0.54 kJ m −2 day −1 ). In the present study, no growth inhibition via subjection to UV-B irradiation was observed under the same conditions.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…As UV-B light sources are being used as artificial lighting to improve phytochemical concentration and to control flowering, it is desirable to provide illumination to an extent that does not impair growth rate and phenotype quality. Using the same light source as that used in the present study, Ota et al [ 21 ] did not report any effect on plant growth under conditions of exposure to 3 h of illumination at 0.05 W m −2 (0.54 kJ m −2 day −1 ). In the present study, no growth inhibition via subjection to UV-B irradiation was observed under the same conditions.…”
Section: Discussionmentioning
confidence: 65%
“…It has been reported that UV-B irradiation decreases the concentration of anthocyanins in red perilla leaves and causes a change in their color to green [ 10 , 21 , 24 ]. In this study, we observed leaf greening due to UV-B irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inconsistent findings may be explained by the fact that plant species have different sensitivity to UV-B radiation in addition to the adverse growth conditions among the different studies such as the ratio of PAR to UV-B radiation during the growth period. The UV-B radiation damage to plants can be reduced by combining UV-B irradiation with visible light (OTA et al, 2017). In Table 1 -Interactive effects of nitrogen and UV-B radiation on shoot, stem and leaves dry matter (g), stomatal conductance (gs, mol m -2 s -1 ), photosynthesis (A, μmol m -2 s -1 ), transpiration (E, mmol m -2 s -1 ), intercellular CO2 concentration (Ci, μmol mol -1 ), total chlorophyll and carotenoid content (mg g -1 FW) activity of peroxidase (PG-POD, μmol min -1 mg -1 protein) and malondialdeyde content (MDA, nmol g -1 fresh weight) of sunflower plants.…”
Section: Resultsmentioning
confidence: 99%